2017
DOI: 10.1111/jeb.13153
|View full text |Cite
|
Sign up to set email alerts
|

Looks matter: changes in flower form affect pollination effectiveness in a sexually deceptive orchid

Abstract: Many species of the sexually deceptive genus Ophrys are characterized by insect-like flowers. Their form has been traditionally considered to play an important role in pollinator attraction and manipulation. Yet, the evolution of the floral form remains insufficiently understood. We hypothesize that pollinator-mediated selection is essential for driving floral form evolution in Ophrys, but that form components are being subjected to varying selection pressures depending on their role in mediating interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The shape and the colour of the flower then induce the male pollinator to land on the flower (e.g. Rakosy et al ., 2012, 2017; Paulus, 2018). The shape (Rakosy et al ., 2017) and the hairiness (Ågren, Kullenberg, & Sensenbaugh, 1984) of the flower orient the body of the male parallel to the longest length of the labellum on the flower.…”
Section: The Bee Orchids and Their Pollinatorsmentioning
confidence: 99%
“…The shape and the colour of the flower then induce the male pollinator to land on the flower (e.g. Rakosy et al ., 2012, 2017; Paulus, 2018). The shape (Rakosy et al ., 2017) and the hairiness (Ågren, Kullenberg, & Sensenbaugh, 1984) of the flower orient the body of the male parallel to the longest length of the labellum on the flower.…”
Section: The Bee Orchids and Their Pollinatorsmentioning
confidence: 99%
“…An important area of future research will be to understand which axes of floral variation experience stronger selection and therefore impose a greater constraint on transitions in pollination strategy to and from sexual deception (e.g. Ellis et al ., ; Rakosy et al ., ). For example, Rakosy et al .…”
Section: Discussionmentioning
confidence: 97%
“…The increase in attempted copulation may reflect more compelling mimicry, as the olfactory and visual cues now coincide, or wasps being more easily able to firmly grasp the fake female rather than struggling to grasp the relatively fine sepal tips. These results suggest that in many sexually deceptive systems, where strong sexual attraction to the labellum may increase the likelihood of pollination (Rakosy et al ., ; de Jager & Peakall, ), producing the odour from the labellum is likely to be the most effective strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both deceptive strategies, it has also been reported that this variation may also be retained through genetic mechanisms in combination with other selective agents (Rakosy et al . ; Xu et al . ).…”
Section: Discussionmentioning
confidence: 99%